Optimizing Hydrothermal Coordination Scheduling for Large Scale Power - Ab Ghani, Mohd Ruddin; Ahmed, Musse Mohamud; Hassan, Ismail (IEEE, 2002)
The TENAGA NASIONAL BERHAD (TNB) system comprises 53 thermal units and 10 hydro plants of 37 generators (80 units). LaGrangian Relaxation (LR) technique, Dantzig-Wolfe Linear Programming, Sub-Gradient Method (SGM) and Branch & Bound (B&B) have been used to relax the LR multipliers for demand and reserve requirements, and decompose the problem into unit-wise initially and thermal and hydro sub-problems finally. The multipliers are then updated at the lower bound level by SGM. B&B along with some heuristics to get a feasible schedule in the hydro-thermal coordination system. The heuristics used is based on programming with C language code that simplifies on/off statuses of Units for Commitment (UC) and scheduling and Economic Load Dispatch (ELD). The TNB costs have been reduced as shown in the results.